2019
DOI: 10.3389/fcell.2019.00202
|View full text |Cite|
|
Sign up to set email alerts
|

NFκB/Orai1 Facilitates Endoplasmic Reticulum Stress by Oxidative Stress in the Pathogenesis of Non-alcoholic Fatty Liver Disease

Abstract: Non-esterified fatty acids (NEFAs) promote de novo lipogenesis, which caused abnormal hepatic lipid accumulation, by the NFκB–Orai1 pathway. Oxidative stress and endoplasmic reticulum (ER) stress have been recognized as key mechanisms in non-alcoholic fatty liver disease (NAFLD) pathogenesis. Whether Orai1 facilitates ER stress by oxidative stress remains unknown. The rat model of NAFLD was constructed by feeding high-fat diet (HFD). BRL-3A cells were treated with NEFAs, Orai1inhibtor BTP2, NFκB inhibitor wogo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Zhang B and co-workers detected in rats fed with HFD increased blood levels of MDA and decreased blood levels of GSH, correlated with hepatic histopathological changes, observed after HE (hematoxylin eosin) staining [40].…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Zhang B and co-workers detected in rats fed with HFD increased blood levels of MDA and decreased blood levels of GSH, correlated with hepatic histopathological changes, observed after HE (hematoxylin eosin) staining [40].…”
Section: Resultsmentioning
confidence: 80%
“…Hypercaloric food (sugar and butter) administered daily to Wistar rats led to hepatic OS even after only 3 weeks. Zhang B and co-workers observed on a BRL-3A cell line that non-esterified fatty acids administration caused a significant decrease of GSH level and a great increase of MDA level [40]. Arya A and co-workers study results revealed increased plasma levels of MDA, ALT and NO metabolites and low levels of plasma SOD [41].…”
Section: Resultsmentioning
confidence: 94%
“…One potential pathway linking NEFAs and telomere length is oxidative stress. Higher circulating levels of NEFAs have been shown to promote de novo lipogenesis, causing abnormal hepatic lipid accumulation and oxidative stress [ 24 ]. Studies have also shown that reduction of NEFAs lowers oxidative stress [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…To induce downregulation of ORAI1, hepatocytes were transfected with 40 pM cattle ORAI1 small interfering (si)RNA (GenePharma, Shanghai, China) and a non-target siRNA (siRNA-mate, Shanghai GenePharma Co. Ltd., Shanghai, China) according to manufacturer's protocols (Zhang et al, 2019). Hepatocytes were cultured in 6-well plates for 48 h with growth medium.…”
Section: Cellular Manipulations Of Oxidative Stress and Orai1 Abundancementioning
confidence: 99%